Thermo Acoustical Excess Parameters of Anisaldehyde- Toluene Mixture at 303.15, 308.15, 313.15 and 318.15 K - Srinivasu, Ch.; Narendra, K.; Kalpana, Ch. (Asian Journal of Chemistry, 2011)
The ultrasonic velocity, density and viscosity in binary liquid mixture of anisaldehyde + toluene have been determined at different temperatures from 303.15-318.15 K over the whole composition range. The data have been utilized to estimate the excess adiabatic compressibility (bE), excess volume (VE), excess intermolecular free length (Lf E), excess internal pressure (pE), excess enthalpy (HE) and excess viscosity (hE) at these temperatures. The excess values have been found to be useful in estimating the strength of the interactions in the liquid mixtures. Analysis of these parameters indicates that there are weak interactions among the components of the binary mixtures.